Historiographic Metafiction and Symbolism in Dan Brown’s The Da Vinci Code (2003) - Hasni , Elhadj Bouzid; Zerouala, Ibrahim; Selt, Affaf Djihan (Faculty of Letters and Foreign Languages Department of English, 2019)
This dissertation is an attempt to provide an analytical view of history, and how it became at a certain point of time neglected, i.e. rejected as an obstacle to the modern beliefs after being in a prestigious position. After that, history became prominent again after the replacement of modern ism by the postmodernist literature, or rather a new genre called the Historiographic Metafiction. This genre aimed to provide the fictional work with a conscious and living quality through ad dressing the reader directly as well as adding real historical events, places and personages for the sake mocking and parodyzing or correcting a misunderstanding. We see that the best example to fulfill such study is by putting Dan Brown’s novel The Da Vinci Code (2003) Under the micro scope. The aim is to make a projection of some studies of what the postmodernist theory came up with on Brown’s controversial claims. On the other hand, there is also a symbolist study apart which seeks to provide dimensional uses of symbolism in order to clarify their importance as a complement to the events